Effects of energy chirp on bunch length measurement in linear accelerator beams. (17th July 2017) - Sabato, L; Arpaia, P; Giribono, A; Liccardo, A; Mostacci, A; Palumbo, L; Vaccarezza, C; Variola, A
Abstract: The effects of assumptions about bunch properties on the accuracy of the measurement method of the bunch length based on radio frequency deflectors (RFDs) in electron linear accelerators (LINACs) are investigated. In particular, when the electron bunch at the RFD has a non-negligible energy chirp (i.e. a correlation between the longitudinal positions and energies of the particle), the measurement is affected by a deterministic intrinsic error, which is directly related to the RFD phase offset. A case study on this effect in the electron LINAC of a gamma beam source at the Extreme Light Infrastructure-Nuclear Physics (ELI-NP) is reported. The relative error is estimated by using an electron generation and tracking (ELEGANT) code to define the reference measurements of the bunch length. The relative error is proved to increase linearly with the RFD phase offset. In particular, for an offset of 7 ∘, corresponding to a vertical centroid offset at a screen of about 1 mm, the relative error is 4.5%.